Adaptation Over a Wide Range of Donor Graft Lung Size Discrepancies in Living‐Donor Lobar Lung Transplantation. Issue 5 (15th March 2013) - Chen, F.; Kubo, T.; Yamada, T.; Sato, M.; Aoyama, A.; Bando, T.; Date, H.
<x xml:space="preserve">Abstract</x> Living‐donor lobar lung transplantation (LDLLT), unlike deceased donor lung transplantation, often involves a wide range of size discrepancies between donors and recipients. The aim of this study was to evaluate the function of donor lung grafts in the recipient thorax in 14 cases of bilateral LDLLT involving 28 successfully transplanted lower‐lobe grafts. Pulmonary function tests and three‐dimensional computed tomography (3D‐CT) volumetry were performed perioperatively. According to 3D‐CT size matching, donor graft volumes ranged from 40% to 161% of the hemilateral thoracic volumes of the recipients. Graft forced vital capacity (FVC) values increased over time, reaching 102 ± 39% of preoperatively estimated values at 12 months postoperatively. Graft volumes also increased over time, reaching 120 ± 38% of the original values at 12 months postoperatively. Undersized donor grafts expanded more after LDLLT than oversized donor grafts, producing greater FVC values than those estimated preoperatively, whereas oversized donor grafts became inflated to their original size and maintained FVC values that approached the preoperative estimates. Thus, donor grafts were found to overinflate or underinflate to the extent that they could preserve their native function in the new recipient's environment.